Dynamics of Adaptation of Interest Rates, Credit, and Economic Activity to the Conditions of Slowing Money Supply Growth in Indonesia - Sanusi Gazali Pane; Suci Ramadhani; Adestia Pibiolah Butar Butar; Shifa Indah Lestari (Yayasan Multidimensi Kreatif, 2025)
In Indonesia, the slowdown in money supply growth (M2) raises concerns about the effectiveness of monetary policy transmission to the real sector. This study aims to analyze the adaptation of key macroeconomic variables, including policy interest rates, credit growth, economic activity, and exchange rates to the slowdown in money supply growth. The method used is a descriptive qualitative approach through literature studies by utilizing secondary data from official publications of Bank Indonesia, the Central Statistics Agency, and related scientific literature. The results show that interest rates respond most quickly as an initial adjustment mechanism, while credit growth and real economic activity adapt gradually. Household consumption plays a role as a support for growth in the short term, while investment is more sensitive to tightening liquidity. Exchange rates adapt through financial market mechanisms and the expectations of economic actors. This study concludes that the slowdown in the money supply does not always have a negative impact on economic stability when balanced with measured and consistent monetary policy.